Why is the equilibrium notion essential for a unified institutional theory? A friendly remark on the article by Hindriks and Guala. Issue 3 (11th March 2015) - AOKI, MASAHIKO
Abstract: This short commentary basically supports the unified approach to institutions of Hindriks and Guala (2014 ). First, using a flow diagram over the two-by-two boxes in the space spanned by the collective-individual dimension and the behavior (play)-cognitive (belief) dimension, it argues that the classical game theory and the so-called institution-as-rule theory are both incomplete and that they should be regarded as complementary for an integrated theory of institution as a process. However, the substantive forms of institutions ought to be linguistic representations (i.e. rules and ideas) that summarize equilibrium states of play of the societal game so as to mediate them to be incorporated into minds of players as collective intentionality (i.e. shared beliefs). From this perspective this note also supports the authors' argument to unpack the 'Y' term in Searle's notion of constitutive rule (that is, the regulative rule) and submit it to be based on a neo-Hegelian notion of mutual recognition (i.e. equilibrium).